A cross sectional study on clinical trends of reproductive performances and reproductive disorders of dairy cows in Rajshahi district of Bangladesh (Asian Journal of Medical and Biological Research, 2020)
Performance evaluation of existing dairying is important to design relevant dairy development strategies and implement context specific interventions for future development of the dairy enterprise. The present study was carried out to evaluate the clinical trends (reproductive performance and disorders) of dairy cows of Rajshahi district, Bangladesh. A total of 500 cows randomly selected and data were collected directly from the dairy farms owners from 6 upazilas and 4 metro thanas of Rajshahi district by using questionnaires and diagnosis of reproductive disorders (RD) was made on the basis of history, clinical signs and response to treatment. The average reproductive performance (RP) were recorded as age at puberty 26.42±0.22 m, age at first calving 35.48±0.22 m, post-partum heat period 121.85±3.48 days, service per conception 1.93±0.04, days open 136.80±3.57 days and calving interval 401.04±3.94 days. The better RP was found at metro thanas compared to upazilas, though no significant difference was found except on service per conception (p